The Influence Of Organizational Competencies And Culture On Employee Performance PT. BPR Majalengka Jabar - Hj. Dharliana Hardjowikarto (SINTESA, 2023)
This study aims to test the influence of competencies and organizational culture on the performance of employees for bpr majalengka jabar. The research method used in this study is the quantitative research method. The population in this study were employees of PT. BPR Majalengka Jabar with a sample number of 64 employees. The sampling technique in this study is saturated sampling, which is a sampling technique that does not give an equal opportunity/opportunity for each element or member of the population to be sampled. Data collection techniques using questionnaires and the results of this study showed that competence had a positive and significant effect on employee performance as seen from thitung > ttable or 3.623 > 1.670, organizational culture had a positive and significant effect on employee performance as viewed from thitung > ttable or 1.889 > 1.670 and simultaneously competence and organizational culture had a significant effect on employee performance was shown Fact > Ftable of 27.120 > 3.145. Of all results both partially and simultaneously have sig values smaller than 0.05 or 0.000